Temperament types and Conflict Management Styles of School Heads in the Public Secondary Schools: An Explanatory Sequential Mixed Method Inquiry - Imperial, Joebel; Madrigal, Dennis; Dioso, Dexter Paul D. (Technium Social Sciences Journal, 2023)
Conflict is manageable when paired with reason and experience. Using explanatory sequential mixed-method, this study determined the extent of practice and explored the insights and experiences of school heads in conflict management styles. For the quantitative phase, frequency count, percentage distribution, mean, spearman rank correlation, and rank biserial were used. The results revealed that school heads generally practiced conflict management styles to a great extent. This means that the five conflict management styles were often observed by the school heads. Meanwhile, both temperament types and demographics do not influence conflict management styles which were also supported by the qualitative results through Lichtman's three Cs: coding, categorizing, and conceptualizing. Thus, in the practice of conflict management, school heads vary in terms of their perspectives, while reasons serve as guiding principles coupled with appropriate approaches. Moreover, it is the administrative experience that really matters in conflict management, not necessarily generational age, sex, and educational attainment. The findings suggest that reason and experience are essential factors of conflict management.